The transforming protein of the MC29-related virus CMII is a nuclear DNA-binding protein whereas MH2 codes for a cytoplasmic RNA-DNA binding polyprotein. - Bunte, T (1983)
The acute avian leukemia viruses MH2 and CMII belong to the group of avian myelocytomatosis viruses, the prototype virus of which is MC29. This group of viruses is characterized by myc-specific oncogenes which are presumably expressed as gag-myc polyproteins. These polyproteins are synthesized in non-producer cells transformed by MH2 and CMII and have mol. wts. of 100 000 (p100) and 90 000 (p90), respectively. Monoclonal antibodies against the N terminus of gag, p19, were used to localize the protein in MH2- and CMII-transformed non-producer fibroblasts. Immunofluorescence and cell fractionation indicated that greater than 90% of p100 from MH2 was located in the cytoplasm, whereas greater than 70% of p90 from CMII resided in the nucleus. Isolation of p100 and p90 by immunoaffinity chromatography resulted in an approximately 2000-fold purification of the two polyproteins. Both of them, as well as p110 of MC29, bound to double-stranded DNA of chick fibroblasts in vitro. However, only the MH2-specific polyprotein p100 bound to RNA in vitro. Such a binding was not observed for p90 or p110, or for the purified gag precursor Pr76. Another polyprotein, gag-erbA, from avian erythroblastosis virus, which is also located in the cytoplasm, did not bind to RNA. Our results indicate that the CMII-specific polyprotein p90 behaved indistinguishably from the p110 of MC29. However, the MH2-specific polyprotein p100 exhibited unique and novel properties which were distinct from a gag-myc-type protein.